PERANCANGAN MESIN RICE TRANSPLANTER UNTUK PADI JENIS JAJAR LEGOWO MENGGUNAKAN METODE VDI 2222 - Jetma Sabilla Sabilla; Nur Akhlis Sarihidaya Laksana; Jenal Sodikin; Ulikaryani; Unggul Satria Jati; Ghia Pisti Cikarge (Politeknik Negeri Cilacap, 2026)
Agricultural mechanization is a key strategy for boosting rice cultivation productivity while addressing labor shortages in the agricultural sector. However, most rice transplanters used in Indonesia are imported products that do not fully align with local paddy field characteristics and entail relatively high investment costs. This study aims to analyze the design process of a rice transplanter tailored for the jajar legowo planting system, utilizing the VDI 2222 method and SolidWorks-based 3D modeling. The analysis covered user requirements, design concept selection, machine dimensions, seedling tray configuration, the *jajar legowo* planting system, and material selection. The results indicate that the optimal design concept features a six-row planting configuration with a frame size of 1085 mm × 1472.6 mm, six seedling trays measuring 218 mm × 600 mm, and a material combination of galvanized steel and stainless steel—balancing structural strength, corrosion resistance, ease of manufacturing, and cost-efficiency. Implementing the jajar legowo system with a planting distance of approximately 20 cm is considered conducive to planting efficiency and compatible with rice cultivation practices in Indonesia. Overall, the design process yielded a rice transplanter model with the potential to be developed into a functional prototype, serving as a more economical local alternative that meets the specific needs of Indonesian farmers.